Eosinophil Counts in the Small Intestine and Colon of Children Without Apparent Gastrointestinal Disease: A Meta-analysis. Issue 1 (July 2018) - Kiss, Zoltán; Tél, Bálint; Farkas, Nelli; Garami, András; Vincze, Áron; Bajor, Judit; Sarlós, Patrícia; Márta, Katalin; Erős, Adrienn; Mikó, Alexandra; Szakács, Zsolt; Pécsi, Dániel; et al.
Abstract : ABSTRACT: The aim of the current study was to review the available data regarding eosinophil density in healthy tissue specimen originating from lower gastrointestinal segments to support suggested diagnostic cutoffs widely used in clinical practice. A systematic search was performed in 3 different databases. Calculations were made with Comprehensive MetaAnalysis software using random-effects model. Cell number measurements were pooled using the random-effects model and displayed on forest plots. Summary point estimations, 95% confidence intervals (CIs), and 95% prediction intervals (PIs) were calculated. The cumulative mean cell numbers were 8.26 (95% CI 4.71-11.80) with PI of 0-25.32 for the duodenum, 11.52 (95% CI 7.21-15.83) with PI 0-60.64 for the terminal ileum, and 11.10/ high-power field (HPF) (95% CI 9.11–13.09) with PI of 0.96 to 21.23 in the large intestine and the rectum (HPF area = 0.2 mm 2 ). Previous studies included control patients with irritable bowel syndrome and functional gastrointestinal disorders. As mucosal eosinophils have a role in their pathomechanism, those patients should have been excluded. A critical point of interpreting reported data is that HPF is relative to the technical parameters of the microscopes; therefore, it is important to report findings in cell/mm 2 . The present meta-analysis does not support the higher (>20) or lower (<10) cutoff values for healthy tissue eosinophil number. In contrast to the esophagus, there is no normal cutoff eosinophil density in the small intestine and the colon. A prospective, multicenter study to establish normal mucosal eosinophil density is clearly needed. Abstract : Supplemental Digital Content is available in the text